ANALISIS PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP MOTIVASI, KEDISIPLINAN DAN KINERJA GURU DI SD ISLAM LUMAJANG - Hadromi, Fathonah Al (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: Education is an important part of the national development process that will determine the progress of a country. Education is also an investment in the construction and development of human resources, with the improvement in skills and capabilities that believed to be a contributing factor in the human attempts to influence life that filled with uncertainty. This study intends to determine the effect of leadership style to the performance of teachers and staffs in SD Islam Tompokersan and SD Islam Al Ikhlas Lumajang, with the motivation and discipline of work as intervening variables. The analytical method used in this research is the empirical analysis with a quantitative approach with the method of Path analysis. The results showed leadership style has negative effect on motivation, leadership style does not affect the discipline of teachers and staffs, motivation significant has positive effect on the performance of teachers and staffs, disciplinary significant has positive effect on the performance of teachers and staffs in SD Islam Tompokersan and SD Al Ikhlas Lumajang, and leadership style does not significantly influence the performance of teachers and staffs, it demonstrates leadership style does not has a linear relationship to the performance of teachers and staffs in SD Islam Tompokersan and SD Al Ikhlas Lumajang.Keywords: Style of school leadership, motivation, work discipline, teacher performance.